(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In some cases, when solving equations, you have to use the properties of a function. In this case, the domain of the function, the properties of boundedness, monotonicity are used. In many cases, the use of the graph of the function can also help in solving equations.